Upaya Meningkatkan Hasil Belajar Mengenal Abjad Dengan Menggunakan Alat Peraga Pada Pembelajaran Bahasa Indonesia Siswa Kelas I SD Naskat Cendana Kecamatan Morotai Jaya - Elsin Kodobo (Jurnal Ilmiah Wahana Pendidikan, 2020)
The aim to be achieved in this study is to determine the Efforts to Improve Learning Outcomes to Know the Alphabet by Using Teaching Aids in Indonesian Language Learning for Class I SD Naskat Cendana, Morotai Jaya District. The type of research used in this research is the Classroom Action Research method which we know as PTK (Classroom Action Research). This research consists of two cycles and in general, there are four stages, namely (1) planning, (2) acting, (3) observing, and (4) reflecting. Based on data analysis and discussion, the conclusion that can be drawn from this study is that the application of teaching aids learning models can improve students' alphabet recognition skills in Indonesian class 1 students of SD Naskat Cendana. The results of the reading skills of students in the first cycle that met the success criteria were 9 students 42.71%, while in the second cycle there was an increase, of the 21 students who met the success criteria were 17 students, 80.24%, and those who had not reached the success of 4 students were 19.76%.